Trade Openness-Government Size Nexus: Compensation Hypothesis Considered for Nigeria - Aregbeyen, Omo; Ibrahim, Taofik Mohammed (Journal of Reviews on Global Economics, 2014)
Over the years, substantial theoretical and empirical studies have been carried out on the trade openness-government size nexus. While a strand of the literature reported positive linkage, the other suggests otherwise. This study contributes to the debate by examining this relationship for Nigeria using the bounds testing approach to cointegration within an ARDL framework proposed by Pesaran et al. (2001). Empirical evidence reveals that government size measured by percentage share of total government expenditure in GDP and share (percent) of recurrent expenditure in GDP significantly affects trade openness in the long run but percentage share of capital expenditure in GDP as a measure of government size does not impact on trade openness in the long run. The results of the standard causality test corroborate these findings. However, the three measures of government size considered significantly affect trade openness in the short run. The major implication for our study therefore is that compensation hypothesis holds for Nigeria. Thus, the government need to continue to expand its expenditure in order to cushion the effect of increase in risk caused by rising trade openness.